2019
DOI: 10.1155/2019/3160562
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of Short Courses to Support the Establishment of a Prehospital System in Sub-Saharan Africa: Lessons Learned from Tanzania

Abstract: Background Tanzania has no formal prehospital system. The Tanzania Ministry of Health launched a formal prehospital system to address this gap. The Muhimbili University of Health and Allied Sciences (MUHAS) was tasked by the Ministry of Health to develop and implement a multicadre/provider prehospital curriculum so as to produce necessary healthcare providers to support the prehospital system. We aim to describe the process of designing and implementing the multicadre/provider prehospital short courses. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A reason for this diference could be the existence of prehospital EMS in South Africa to treat and transport acutely sick or injured patients to the hospital as opposed to our setup, which lacks this formal system [2,18]. Te majority of patients arrived at the initial facility during the "golden hour", yet the median time to reach the EMD, which is a trauma center, was slightly over 6 hours.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A reason for this diference could be the existence of prehospital EMS in South Africa to treat and transport acutely sick or injured patients to the hospital as opposed to our setup, which lacks this formal system [2,18]. Te majority of patients arrived at the initial facility during the "golden hour", yet the median time to reach the EMD, which is a trauma center, was slightly over 6 hours.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, a study conducted in South Africa found the prevalence of polytrauma to be sixfold higher [ 2 ]. A reason for this difference could be the existence of pre-hospital EMS in South Africa to treat and transport acutely sick or injured patients to the hospital as opposed to our setup, which lacks this formal system [ 2 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most advanced curriculum was a 6 weeklong course and was the only one to include medical emergencies among the core content. Only a fraction of their lay providers received this education [18]. Similar to our course, in Botswana, a novel two-day course was developed and implemented for Ministry of Health-sponsored pre-hospital providers.…”
Section: Discussionmentioning
confidence: 99%
“…A hospital-based or local (municipality level fire department or legal enforcement) model can also be used to organize a tier-two system that provides professional prehospital care within a defined jurisdiction and will be linked to the tier-one system (3,6). Moreover, Mould-Millman et al (18) have clearly Perspective PAJEC outlined the steps towards establishing such a two-tier emergency medical dispatch system in small-and large-scale areas in the African context, while success stories have been reported in a few countries on the continent (7,(19)(20)(21)(22)(23)(24) and countries on other continents such as Pakistan (25). Nevertheless, organizing and sustaining PHC systems, in particular a large-scale two tier system continued to be challenging both technically and financially in resource-limited settings, primarily in many African countries (26)(27)(28)(29).…”
Section: Model For Phc Systems In Resourcelimited Settingmentioning
confidence: 99%